EVALUATION OF CARDIOPROTECTIVE EFFECT OF DAIDZEIN IN 5-FLUOROURACIL-INDUCED CARDIOTOXICITY IN WISTAR RATS - Vivek Srivastavaa; Bushra Khatoona Utkarsh Upadhyay
The aim of the study was to determine the cardioprotective effect of daidzein in 5-fluorouracil-induced cardiotoxicity. The animals of the standard group were treated with carvedilol 10 mg kg-1, and DDZ5 and DDZ10 groups were treated with daidzein for 8 days at doses of 5 mg kg-1 and 10 mg kg-1, respectively, with induction of disease on day 5 with 5-fluorouracil in all groups. The results were determined by evaluating biochemical parameters such as CK-MB, LDH, cTnl, GSH, MDA, MPO and total cholesterol, as well as histopathological study. It was found that both daidzein 5 mg kg-1 and daidzein 10 mg kg-1 considerably (p<0.01) decreased the animal's levels of MDA, MPO, LDH and CKMB compared to the negative control group. The level of GSH in DDZ5 and DDZ10 animals was significantly (p<0.01) higher than negative control animals. It can be concluded from this study that daidzein holds significant potential to prevent as well as manage the cardiotoxicity caused by 5-FU.